Higher general executive functions predicts lower body mass index by mitigating avoidance behaviors - La Marra, Marco; Ilardi, Ciro Rosario; Villano, Ines; Polito, Rita; Sibillo, Maria Raffella; Franchetti, Marina; Caggiano, Angela; Strangio, Francesca; Messina, Giovanni; Monda, Vincenzo; Di Maio, Girolamo; Messina, Antonietta (Frontiers in Endocrinology, 2022)
Background: The present study examines the relationship between obesity, executive functions, and body image in a nonclinical sample from southern Italy. Methods: General executive functioning (Frontal Assessment Battery–15), and Body image disturbances (Body Uneasiness Test) were assessed in a sample including 287 participants (155 females, M age=43.51 years, SD = 17.94, range = 18–86 years). Findings: Multiple Linear Regression Analysis indicated that age, years of education, FAB15 score, Body image concerns, and Avoidance negatively predicted BMI. A subsequent mediation analysis highlighted that the indirect effect of FAB15 on BMI through Avoidance was statistically significant. Interpretation: Our results suggest that executive function significative affect BMI. Still, we found that the avoidance dimension partially mediates the dynamics of such a relationship